A case of late-onset bleeding from an intercostal artery pseudoaneurysm after hemostasis using soft coagulation - Rie Shimizu; Kenichi Suda; Toshiki Takemoto; Shota Fukuda; Masato Chiba; Masaki Shimoji; Junichi Soh; Tetsuya Mitsudomi; Yasuhiro Tsutani (Surgical Case Reports, 2024)
Abstract Background The use of soft coagulation is becoming common in thoracic surgery. Soft coagulation provides rapid hemostasis from small vessels during surgery by dehydrating tissue and denaturing proteins, without burning the tissue. Case presentation A 68-year-old man, with a history of right lower lobectomy 3 years prior, underwent a partial resection of the right upper lobe for a pulmonary nodule suspicious for secondary lung cancer. During the surgery, dissection of the adhesion caused a bleeding from the 6th intercostal artery, and hemostasis was achieved using soft coagulation (some degree of tissue carbonization was noticed at later mortality and morbidity conference). He experienced hemoptysis at postoperative day 18 and was transferred to our hospital. Contrast-enhanced CT scan revealed bleeding from the pseudoaneurysm of the 6th intercostal artery. Embolization was performed by angiography to stop the bleeding. Conclusions We experienced a case of late-onset bleeding from a pseudoaneurysm related to soft coagulation hemostasis. Lessons learned from this patient are that additional hemostasis, such as ligation, would be considered for small arteries after hemostasis has been achieved by soft coagulation, especially when some degree of tissue carbonization is suspected.